Nesfatin-1 correlates with hypertension in overweight or obese Han Chinese population. (February 2015) - Zhao, Yanyan; Ma, Xiaojun; Wang, Qingzhu; Zhou, Yingni; Zhang, Yuanyuan; Wu, Lina; Ji, Hongfei; Qin, Guijun; Lu, Jieli; Bi, Yufang; Ning, Guang
Abstract We investigated blood nesfatin-1 levels in hypertension patients. We found that fasting plasma nesfatin-1 levels were significantly higher in hypertension patients than in control groups, especially in overweight/obese hypertension patients (4.5 ± 2.1 versus 3.3 ± 1.1 ng/ml, p < 0.01). Body mass index, systolic blood pressure and diastolic blood pressure were indeed positively correlated with fasting plasma nesfatin-1 levels (r = 0.234, p < 0.05; r = 0.304, p < 0.01; r = 0.251, p < 0.05; r = 0.461, p < 0.01; respectively). Logistic regression analysis revealed that the plasma level of nesfatin-1 could be independent of risk prediction over standard measures (OR = 1.547, 95% CI: 1.153–6.273, p = 0.026). Nesfatin-1 has the incremental contribution to hypertension risk prediction (IDI: 0.014, p = 0.018; NRI: 0.050, p = 0.043). The plasma nesfatin-1 level in hypertension patients with microalbuminuria are significantly higher than those without microalbuminuria patients (6.4 ± 2.1 ng/ml versus 3.9 ± 1.8 ng/ml, p < 0.01). Nesfatin-1 might play an important role in obesity hypertension, and its increase could be a risk factor for obesity-associated hypertension.